Melamine Detection in Food matrices employing Chicken Antibody (IgY): A Comparison between Colorimetric and Chemiluminescent Methods - Sushma, Umesh; Srivastava, Alok K.; Krishnan, Manonmani H. (Current Analytical Chemistry, 2019)
Background: Melamine, contains 67% nitrogen by mass, and is adulterated in foods to uplift false protein. There is an urgent requirement to develop fast screening techniques for monitoring melamine in foods. Objectives: To develop rapid, high throughput detection techniques for melamine in the food matrix. Methods: IgY antibodies were developed against melamine in the hen, isolated and used for detection of melamine. The detection by colorimetric and chemiluminescent methods was compared. Results: The detection range for melamine was 1 ng-25 μg by the colorimetric method and 10 fg/mL-25 ng/mL by the chemiluminescent method. There was a very low matrix effect, where the recovery was 86 to 106 % by colorimetric method and 71 to 98 % by the chemiluminescent method. Conclusion: Both colorimetric and chemiluminescent methods could be employed for the fast and consistent melamine detection in the food matrix.
Keywords: enzyme-linked immunosorbent assay (ELISA)